The Influence Of Non-Physical Work Environment And Career Development On Intrinsic Motivation Of Civil Servant Teachers At Smti Vocational High School Pontianak - Jumiati, Selly; Ahmadia, Eru (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
To improve students' learning outcomes, 21st-century educational development demands innovative and efficient teaching approaches. This study examines the intrinsic motivation of teachers at SMTI Vocational High School Pontianak and the influence of the non-physical work environment and career development. The research background highlights the importance of understanding what drives teachers' motivation, as it is critical for enhancing overall educational performance. Intrinsic motivation is crucial; however, few studies have explored the relationship between career development and the non-physical work environment. Involving 62 civil servant teachers from SMTI Vocational High School Pontianak, this study employed an associative quantitative research design. Data were collected using a structured questionnaire with a Likert scale ranging from 1 to 5. The data were then analyzed using multiple linear regression. The findings reveal that intrinsic motivation is significantly influenced by the non-physical work environment and career development. Teachers' intrinsic motivation (Y) can be enhanced by improving the non-physical work environment (X1) and career development (X2), as shown by the regression equation Y = 1.921 + 0.250X1 + 0.316X2 + e. A strong relationship between the variables is indicated by the correlation coefficient (R = 0.670). Meanwhile, the coefficient of determination (R2 = 0.449) shows that the two independent variables account for 44.9% of the variation in intrinsic motivation. In summary, this study emphasizes the importance of enhancing teachers' intrinsic motivation by creating a supportive work environment and well-organized career development programs. Future research should explore other factors influencing motivation, such as organizational culture and leadership style, to gain a deeper understanding of the dynamics of teacher performance.